Genetic Diversity of Maize Accessions (Zea mays L.) Cultivated from Europe Using Microsatellites Markers - Vivodík, Martin; Petrovičová, Lenka; Balážová, Želmíra; Gálová, Zdenka (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Maize (Zea mays L.) or corn is a plant belonging to the family Poaceae and is one of the most important cereal crops worldwide as human nutrient, a basic element of animal feed and raw material for manufacture of many industrial products. Maize is the oldest plant to have a fully established gene map with the basic genome consisting of 10 chromosomes and is an excellent plant for the detection of genotoxins, mutagenic and clastogenic substances in the environment. The SSR molecular markers were used to assess genetic diversity in 20 old European maize genotypes. Five SSR primers revealed a total of 33 alleles ranging from 5 (UMC1962) to 8 (UMC1370) alleles per locus with a mean value of 6.60 alleles per locus. Variations in DNA sequences lead to polymorphism. Greater polymorphism is indicative of greater genetic diversity. The PIC values ranged from 0.780 (UMC1962) to 0.842 (UMC1370) with an average value of 0.814 and the DI value ranged from 0.794 (UMC1962) to 0.848 (UMC1370) with an average value of 0.823. 100% of used SSR markers had PIC and DI values higher than 0.7 that means high polymorphism of chosen markers used for analysis. Probability of identity (PI) was low ranged from 0.005 (UMC1241 and UMC1370) to 0.011 (UMC1859) with an average of 0.007. A dendrogram based on UPGMA analysis separated 20 maize genotypes into two clusters. First cluster contained two maize genotypes Bučiansky Konsky Zub (SK) and Moldavskaja (SUN). Cluster two was divided into two main cluster 2a and 2b. SSR markers are useful in the assessment of maize diversity, the detection of duplicate sample in genotypes collection, and the selection of a core collection to enhance the efficiency of genotypes management for use in maize breeding and conservation.